Answer:
39+4x
Step-by-step explanation:
Since two opposites add up to zero, remove them from the expression
2x3-5x+2+4x2+6x-2x+7x5
Calculate the sum or difference
39+6x-2x
The answer is <span><span>2 <span>1/3 i know bc i just did the test and got it wrong with the other answer </span></span></span>
The required composite value f(g(-8) is 28
A composite function is a function inside another function. Given the following functions
f(x) = x² - 3x - 12
g(x) = -x - 12
Required composite function is f(g(-8))
First we need to get f(g(x))
f(g(x)) = f(-x-12)
f(-x-12) = (-x-12)² - 3x - 12
Expand
f(-x-12) = x² +24x + 144 - 3x - 12
f(-x-12) = x² +21x + 132
f(g(x)) = x² +21x + 132
Substitute x = -8 into the result
f(g(-8)) = (-8)² +21(-8) + 132
f(g(-8)) = 64 - 168 + 132
f(g(-8)) = 28
Hence the required composite value f(g(-8) is 28
Learn more here : brainly.com/question/3256461